The Proceedings of the 5th Asia-Pacific Drying Conference 2007
DOI: 10.1142/9789812771957_0162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drying Temperature and Moisture Content on Rice Taste Quality

Abstract: The influence of drying temperature on rice taste quality was studied in this paper. The heated-air temperature of 40℃, 45℃, 50℃, 55℃, and 60℃, respectively, were used to dry fresh paddy. The critical drying temperature of 45℃ for paddy rice with an initial moisture content of 21.36% w.b. was obtained, which induce the rice taste value declining significantly. Also, the amorphous starch matrix inside the rice kernel, which takes the shape of hardly dissolved starch granular, was observed by electron microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 3 publications
1
21
1
Order By: Relevance
“…This result was supported by Zheng and Lan (2007), as it was noted that ozone caused oxidation to rice kernel that eventually lowers surface moisture content of rice. This is an added-advantage to pest control management as lower moisture content discouraged insect infestation in the grain.…”
Section: Preliminary Studiesmentioning
confidence: 56%
See 1 more Smart Citation
“…This result was supported by Zheng and Lan (2007), as it was noted that ozone caused oxidation to rice kernel that eventually lowers surface moisture content of rice. This is an added-advantage to pest control management as lower moisture content discouraged insect infestation in the grain.…”
Section: Preliminary Studiesmentioning
confidence: 56%
“…Thus, it is recommended that the moisture content of ozone-treated rice to be monitored closely as not to cause any detrimental effect on the rice quality. In a study done by Zheng and Lan (2007), it was observed that moisture content of rice had a direct relation to taste quality. Fatty acid content of rice increased as moisture content drops which results in a higher degree of rice aging and restrains starch gelatinization during rice cooking.…”
Section: Preliminary Studiesmentioning
confidence: 99%
“…Maawuwoe coop brown rice (MCBR) had higher moisture content of 15.17% which may be attributed to its drying temperature used [12]. The relatively higher moisture content of MCBR may have effect on its storage.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…The relatively higher moisture content of MCBR may have effect on its storage. Long grain parboiled rice (LGPR) and Shigafa white rice (SWR) had the least percentage moisture of 12.07% and 11.46% respectively which may be due to the parboiling process [12] and may have the potential to store relatively longer. The significant difference observed in the moisture content of the rice varieties may be attributed to temperature and duration of drying as well as difference in storage conditions at source.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…It is also seen that the effect of temperature is more important than air velocity effect, however if both air parameters are considered together, the drying effect is higher. The work in [19] presents the influence of drying temperature on rice taste quality. Dimensions are important factor of paddy to be studied for quantitative analysis of heat penetration and requirement.…”
Section: Introductionmentioning
confidence: 99%